Pengaruh Ekstraksi Maserasi Menggunakan Pelarut Etanol 70% dan Etanol 96% Terhadap Kadar Flavonoid Total pada Rumput Laut Coklat (Sargassum polycystum) - Meyriska Muna Anissa; Dwi Kurnia Putri; Rose Intan Perma Sari; Tri Danang Kurniawan; Samwilson Slamet (Universitas Pahlawan Tuanku Tambusai, 2026)
Brown seaweed Sargassum polycystum is a natural resource with significant potential as a source of bioactive compounds, particularly flavonoids, which are known for their antioxidant properties. The extraction process plays a crucial role in determining the yield of these compounds, especially the type and concentration of the solvent used. This study aims to evaluate the effect of using 70% ethanol and 96% ethanol as solvents in the maceration method on the total flavonoid content of Sargassum polycystum extract. The samples were collected from Air Langkap Beach, South Bengkulu, then dried, powdered, and subjected to maceration using both solvents with the same solvent-to-material ratio. The obtained extracts were concentrated and analyzed for total flavonoid content using UV-Visible spectrophotometry with aluminum chloride (AlCl₃) reagent and quercetin as a standard. Measurements were conducted at the maximum wavelength obtained from scanning, and the results were expressed as milligrams of quercetin equivalent per gram of extract (mg QE/g). Data were statistically analyzed using parametric or non-parametric tests depending on data distribution to determine significant differences between treatments. The results are expected to show differences in total flavonoid content between extracts obtained using 70% and 96% ethanol, thereby identifying the more effective solvent for extracting flavonoids from Sargassum polycystum. This study is expected to contribute to the development of extraction methods and the utilization of seaweed as a pharmaceutical raw material.